Cannabidiol and amisulpride improve cognition in acute schizophrenia in an explorative, double-blind, active-controlled, randomized clinical trial - Leweke, F. Markus; Rohleder, Cathrin; Gerth, Christoph W.; Hellmich, Martin; Pukrop, Ralf; Köthe, Dagmar (Frontiers in pharmacology, 2021)
Cannabidiol (CBD), a principal phytocannabinoid constituent, has demonstrated antipsychotic properties in recent clinical trials. While it has also been suggested a promising candidate for the treatment of neurodegenerative disorders, it failed to demonstrate efficacy in cognitive impairments associated with schizophrenia as an add-on treatment (600 mg/day for six weeks) in 18 chronically ill patients co-treated with a variety of psychopharmacologic drugs. Here, we report on the results of parallel-group, active-controlled, mono-therapeutic, double-blind, randomized clinical trial (CBD-CT1; ClinicalTrials.gov identifier: NCT00628290) in 42 acute paranoid schizophrenic patients receiving either CBD (up to 800 mg/day) or amisulpride (AMI, up to 800 mg/day) for four weeks in an inpatient setting with neurocognition as a secondary objective. Twentynine patients (15 and 14 in the CBD and AMI group, respectively) completed two cognitive assessments at baseline and the end of the treatment period. We investigated the following cognitive domains: pattern recognition, attention, working memory, verbal and visual memory and learning, processing speed, and verbal executive functions. When applying the Bonferroni correction for multiple testing, p<0.0004 would indicate statistical significance. There was no relevant difference in neurocognitive performance between the CBD and the AMI group at baseline, and we observed no post-treatment differences between both groups. However, we observed improvements within both groups from pre- to post-treatment (standardized differences reported as Cohen’s d) in visual memory (CBD: 0.49, p=0.015 vs. AMI: 0.63, p=0.018) and processing speed (CBD: 0.41, p=0.004 vs. AMI: 0.57, p=0.023). Furthermore, CBD improved sustained attention (CBD: 0.47, p=0.013, vs. AMI: 0.52, p=0.085), and visuomotor coordination (CBD: 0.32, p=0.010 vs. AMI: 0.63, p=0.088) while AMI led to enhanced working memory performance in two different paradigms (Subject Ordered Pointing Task - AMI: 0.53, p=0.043 vs. CBD: 0.03, p=0.932 and Letter Number Sequencing - AMI: 0.67, p=0.017 vs. CBD: 0.08 p=0.755). There was no relevant correlation between changes in neurocognitive parameters and psychotic symptoms or anandamide serum levels. This study shows that both CBD and AMI improve neurocognitive functioning with comparable efficacy in young and acutely ill schizophrenia patients via an anandamide-independent mechanism.
Gesehen am 27.05.2021